KRONİK ANAL FİSSÜR OLGULARINDA CERRAHİ TEDAVİ - ERSAN, Yılmaz; YAVUZ, Nihat; KUŞASLAN, Ramazan; ÇİÇEK, Yusuf and ERGÜNEY, Sabri (Cerrahpaşa Medical Journal, 2014)
Background.- Chronic anal fissure (Chronic fissure in ano) is a longitudinal or pear-shaped defect of the anal canal mucosa extending usually from the dentate line to the external verge of the anal canal. Circular fibers of the internal anal sphincter are visible on the floor of the fissure and secondary changes; such as a sentinel tag, hypertrophied anal papilla and a degree of anal stenosis frequently accompany chronic fissures. A fissure in ano may occur at any age, but is most common between the third and fourth decades. The most dominant symptoms are pain and rectal bleeding. Patients with chronic anal fissure have significantly higher resting anal canal pressures, owing to the overactivity of the internal anal sphincter. Furthermore, recent researches have shown the blood flow to the posterior midline of the anus to be potentially deficient, being supplied by end arteries which pass through the internal sphincter. Finally, a small proportion of all chronic fissures develop after vaginal delivery. The treatment of chronic anal fissures has shifted in recent years from surgical to medical Design.- This study was designed to review the surgical treatments of patients with chronic anal fissure and a medline database was used to perform a literature search for articles relating to the surgical treatment. Conclusion.- Various pharmacologic agents have been shown to lower resting anal pressure and promote fissure healing. This so-called chemical sphincterotomy has become accepted as first –line treatment for chronic anal fissures in many centers. First-line use of medical treatments cures most chronic fissures. If medical treatment fails or fissures recur, sphincter assessment by anal ultrasonography and anal manometry is advised before surgery. If these patients have raised resting anal pressures, lateral internal sphicterotomy approaches should be offered to patients. Although traditional surgical sphincterotomy is very successful at healing chronic anal fissures, it is associated with significant morbidity (incontinence and others) at least, in some series. Whereas, a conservative lateral sphincterotomy (‘Tailored’ approach) results in adequate fissure healing and a much lower incontinence rate to flatus fluid and faeces by preserving more of internal anal sphincter. When there is history of obstetric trauma or previous anal surgery anal ultrasonography and anal manometry may help in identifying, previously unrecognized sphinteric injuries. If the sphincters are compromised, anal advancement flap should be performed. Also, surgical treatment should be performed in patients with chronic anal fissure associated with anal fistula or abscess. New surgical treatments are examined in the context of traditional management of the disease and a future treatment algorithm is suggested.